Adaptive Gene Expression in Bacillus subtilis Strains Deleted for tetL - Wei, Yi (American Society for Microbiology, 2006)
The growth properties of a new panel of Bacillus subtilis tetL deletion strains and of a derivative set of strains in which tetL is restored to the chromosome support earlier indications that deletion of tetL results in a range of phenotypes that are unrelated to tetracycline resistance. These phenotypes were not reversed by restoration of a tetL gene to its native locus and were hypothesized to result from secondary mutations that arise when multifunctional tetL is deleted. Such genetic changes would temper the alkali sensitivity and Na(+) sensitivity that accompany loss of the monovalent cation/proton activity of TetL. Microarray comparisons of the transcriptomes of wild-type B. subtilis, a tetL deletion strain, and its tetL-restored derivative showed that 37 up-regulated genes and 13 down-regulated genes in the deletion strain did not change back to wild-type expression patterns after tetL was returned to the chromosome. Up-regulation of the citM gene, which encodes a divalent metal ion-coupled citrate transporter, was shown to account for the Co(2+)-sensitive phenotype of tetL mutants. The changes in expression of citM and genes encoding other ion-coupled solute transporters appear to be adaptive to loss of TetL functions in alkali and Na(+) tolerance, because they reduce Na(+)-coupled solute uptake and enhance solute uptake that is coupled to H(+) entry.